Flight motor networks modulate primary olfactory processing in the moth Manduca sexta - Chapman, Phillip D. (Proc Natl Acad Sci U S A, 2018)
Nervous systems must distinguish sensory signals derived from an animal’s own movements (reafference) from environmentally derived sources (exafference). To accomplish this, motor networks producing reafference transmit motor information, via a corollary discharge circuit (CDC), to affected sensory networks, modulating sensory function during behavior. While CDCs have been described in most sensory modalities, none have been observed projecting to an olfactory pathway. In moths, two mesothoracic to deutocerebral histaminergic neurons (MDHns) project from flight sensorimotor centers in the mesothoracic neuromere to the antennal lobe (AL), where they provide the sole source of histamine (HA), but whether they represent a CDC is unknown. We demonstrate that MDHn spiking activity is positively correlated with wing-motor output and increased before bouts of motor activity, suggesting that MDHns communicate global locomotor state, rather than providing a precisely timed motor copy. Within the AL, HA application sharpened entrainment of projection neuron responses to odor stimuli embedded within simulated wing-beat–induced flows, whereas MDHn axotomy or AL HA receptor (HA-r) blockade reduced entrainment. This finding is consistent with higher-order CDCs, as the MDHns enhanced rather than filtered entrainment of AL projection neurons. Finally, HA-r blockade increased odor detection and discrimination thresholds in behavior assays. These results establish MDHns as a CDC that modulates AL temporal resolution, enhancing odor-guided behavior. MDHns thus appear to represent a higher-order CDC to an insect olfactory pathway; this CDC’s unique nature highlights the importance of motor-to-sensory signaling as a context-specific mechanism that fine-tunes sensory function.